5-Aminosalicylic Acid Alters the Gut Bacterial Microbiota in Patients With Ulcerative Colitis - Xu, Jun; Chen, Ning; Wu, Zhe; Song, Yang; Zhang, Yifan; Wu, Na; Zhang, Feng; Ren, Xinhua; Liu, Yulan (Frontiers in Microbiology, 2018)
Background The aim of this study was to clarify the effect of 5-aminosalicylic acid (5-ASA) treatment on gut bacterial microbiota in patients with ulcerative colitis (UC). Methods A total of 57 UC patients, including 20 untreated and 37 5-ASA-treated, were recruited into an exploration cohort. We endoscopically collected both noninflamed and inflamed mucosal samples from all patients, and compared the gut bacterial profiles using 16S rDNA sequencing. Ten untreated UC patients were then treated with 5-ASA and subsequently recruited for an independent validation study to confirm the acquired data. Results In untreated UC patients, compared with those in non-inflamed mucosae, Firmicutes (such as Enterococcus) were decreased and Proteobacteria (e.g., Escherichia-Shigella) were increased in the inflamed mucosae. Compared with the inflamed mucosae of untreated UC patients, there was a higher abundance of Firmicutes (e.g., Enterococcus) and lower Proteobacteria (Escherichia-Shigella) in the inflamed mucosae of 5-ASA treated UC patients. In the validation cohort, after administration of 5-ASA, bacterial alteration was consistent with these data. Furthermore, there was a skewed negative correlation between Escherichia-Shigella and bacterial genera of Firmicutes in the inflamed mucosae. 5-ASA treatment decreased the strength of bacterial correlation and weakened the skewed negative correlation pattern. Conclusions The microbial dysbiosis (mainly characterized by an increased abundance in the Escherichia-Shigella genus) and the skewed negative correlation between Escherichia-Shigella and bacterial genera of Firmicutes are two characteristics of the inflamed mucosae of UC patients. 5-ASA treatment decreases Escherichia-Shigella and weakens the skewed correlations, which may be related to its treatment efficiency.